PENGARUH INSIDER OWNERSHIP, KEBIJAKAN HUTANG DAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Kompas 100 Periode 2010-2016) - Lili Salfina; Vivi Riani (Ensiklopedia of Journal, 2019)
This research was conducted to determine the effect of Insider Ownership, Debt Policy, Dividends on Company Value in Kompas 100 in 2010-2016. The purpose of this study was to analyze the effect of Insider Ownership, Debt Policy and Dividends on the value of the company, which was registered in Kompas 100 Company in 2010-2016. The population in this study were Kompas 100 companies listed in the Indonesia Stock Exchange (BEI) in 2010-2016, the sampling method in this study used purposive sampling method. There are 5 companies that meet the criteria as research samples so that the research data is 35. The type of data used is quantitative data. Data analysis techniques used are descriptive statistics, classical assumption test using normality test, multicollinearity test, multiple linear regression analysis using partial hypothesis testing (T test) and simultaneous test (F test) SPSS 16 for Windows. In this study obtained from financial statements that are willing on the Indonesia Stock Exchange (IDX) in 2010-2016. The results showed that Insider Ownership,T test Insider Ownership0,318>0,05 and F test Debt Police no signifikan 0,396>0,05 dan dividendssignifikan 0,19